Structural, thermal morphological, and magnetic properties of Ni1−xLaxFe2−xCsxO4 (x = 0.1,0.2) spinel ferrite prepared via coprecipitation method - Sani, Yusuf; Syahidah Azis, Raba'ah; Ismail, Ismayadi; Yaakob, Yazid; Abdul Karim, Muhammad Khalis; saad, Nor Kamilah; Mohammed, J. (Elsevier B.V., 2024)
In this work, co-precipitation was used to synthesize Ni1−xLaxFe2−xCsxO4 (x = 0.1, 0.2) ferrite ceramic nanoparticles. Based on structural analyses, it can be shown that the nanoscale particles exhibit a single-phase cubic spinel structure and visible particle aggregation. The lattice parameters that are computed using the suggested cation distribution exhibit a strong correlation with the reported values. FESEM and HRTEM surface morphology investigations reveal somewhat aggregated, spherically-shaped nanoparticles. The analysis of EDX verifies the anticipated stoichiometry. The materials' soft magnetic behavior is demonstrated by the VSM study's saturation magnetization (Ms). Magnetic coercivity, retentivity, and saturation magnetization all increased with increasing La3+ ion concentration. In addition, the magnetic quality factor (Q) improved, the saturation magnetization (Ms) increased from 72.937 to 77.691 emu/g, and the coercivity (Hc) increased from 94.256 to 98.521 Oe. More significantly, for the La3+-substituted ferrite samples, the resonance frequency rose in concordance with the La3+ ion concentration. In general, the substitution of rare earth La3+ ions for Ni-Cs ferrite expands the applications of ferrite ceramics in radio frequency and microwave devices. This allows these materials to be used for high-frequency electronics, efficient electromagnets, magnetic data storage, and magnetic field sensing. © 2024 Elsevier B.V.